Evaluation of Direct-acting Antiviral Drugs for Hepatitis C patients below 30 years age in Sialkot, Pakistan - Kashif Waqas, Bushra Noreen, Zoya Muzaffar, Furqan Sabir, S. Z. Haider Naqvi, J. Anver Qureshi, Faheem Hadi, M. Khawar Abbas (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infection of Hepatitis C virus (HCV) is major contributor in liver problems, affecting nearly more than 70 million people all over the world. Top ten countries which are affected by Hepatitis, also include Pakistan. Medical science has entered a new era of HCV therapy in elimination of infection and disease is a real possibility. In asia, Genotype 3 is chronic hepatitis C genotype as compared to other genotypes. Direct-acting antiviral drugs are famous for their high efficacy rate, but less work has done in Asia. Methods: A follow up research was performed to evaluate 3 months treatment outcome of some direct acting antiviral drugs in 35 patients (26 patients of HCV genotype 3) below 30 years of age using some relevant biological parameters. Results: A total of 30 patients yielded a pooled SVR of more than 85% after twelve weeks outcome of commonly used antiviral drugs evaluation. Conclusion: Commonly used antiviral drugs in Sialkot, Pakistan showed effectiveness in HCV pts having genotypes 1, 2, 3 & 5. Keywords: Hepatitis C virus, genotype 3, direct acting antiviral drugs, liver function tests, renal function tests